Frailty Is Associated With Increased Rates of Acute Cellular Rejection Within 3 Months After Liver Transplantation. Issue 3 (3rd February 2020) - Fozouni, Laila; Mohamad, Yara; Lebsack, Adrienne; Freise, Chris; Stock, Peter; Lai, Jennifer C.
Abstract : Frailty, a state of decreased physiological reserve, has been associated with dysregulation of the immune system. We hypothesized that frailty is associated with differential rates of acute cellular rejection (ACR) in liver transplantation (LT) recipients. Our study included LT recipients from 2014 to 2016 who had a pre‐LT frailty assessment using the liver frailty index (LFI). Frailty was defined as an LFI ≥4.5. ACR at 3 months was ascertained from pathology reports, and immunosuppression regimens were collected from chart review. There were 241 LT recipients who were included: 46 (19%) were classified as frail before LT. Median tacrolimus trough levels, mycophenolate doses, and corticosteroid doses at discharge and 3 months were similar between frail and nonfrail patients. Within 3 months after LT, 7 (15%) frail patients versus 10 (5%) nonfrail patients experienced ACR ( P  = 0.02). In the univariate analysis, frailty was associated with a higher odds of ACR at 3 months (OR, 3.3; 95% confidence interval, 1.2‐9.3; P  = 0.02). Bivariate analyses were conducted with covariates that were associated with ACR in the univariate analysis or that were previously associated with either frailty (age and female sex) or ACR (Model for End‐Stage Liver Disease score and ascites), as well as relevant immunosuppression variables. In the bivariate analyses, frailty remained significantly associated with ACR at 3 months with an odds ratio relatively similar to the unadjusted value. In conclusion, frailty is associated with an increased rate of ACR within 3 months, despite similar immunosuppression regimens, suggesting that frailty should be considered in immediate post‐LT management.